DETECTION OF GASTROINTESTINAL PARASITES IN GOATS (CAPRA HIRCUS) IN BARILI, CEBU, PHILIPPINES - Resuelo, Junalyn D.; Talle, Maxfrancis G.; Perez, Zandro O.; Ybañez, Rochelle Haidee D.; Ybañez, Adrian P. (Journal of Agriculture and Technology Management, 2018)
Gastrointestinal (GIT) parasites are known to affect the health of goats. In the Philippines, data on caprine GIT parasites are limited. The present study aimed to provide information on the presence of GIT parasites in goats in Cebu, Philippines. A total of 205 goats were sampled from three different areas in Barili, Cebu, Philippines. Fresh fecal samples were evaluated using the direct fecal smear method. From those found positive, selected samples were processed for larval culture for a more specific identification. Results revealed that 66.3% (136) were positive with GIT parasites, including Eimeria, Strongyloides, and Trichuris spp. Examination of the cultured larvae also revealed the presence of Bunostomum , Teladorsagia, Haemonchus and Cooperia spp. The present study revealed that majority of the goat samples were positive for GIT parasites, which calls for the implementation of a deworming program.